Paucatalinone A from Paulownia Catalpifolia Gong Tong Elicits mitochondrial-mediated cancer cell death to combat osteosarcoma - Wang, Ganyu; Cui, Zhiwei; Tian, Jinqiu; Li, Xinyuan; Tang, Wenzhao; Jing, Weiqiang; Li, Aiwu; Zhang, Yuankai (Frontiers in Pharmacology, 2024)
As the global cancer burden escalates, the search for alternative therapies becomes increasingly vital. Natural products, particularly plant-derived compounds, have emerged as promising alternatives to conventional cancer treatments due to their diverse bioactivities and favorable biosafety profiles. Here, we investigate Paucatalinone A, a newly discovered geranylated flavanone derived from the fruit of Paulownia Catalpifolia Gong Tong, notable for its significant anti-cancer properties. We revealed the capability of Paucatalinone A to induce apoptosis in osteosarcoma cells and deciphered its underlying mechanisms. Our findings demonstrate that Paucatalinone A substantially augments apoptosis, inhibits cell proliferation, and demonstrates a pronounced anti-tumor effect in a murine model of osteosarcoma. Mechanistically, Paucatalinone A disrupts calcium homeostasis and exacerbates intracellular reactive oxygen species accumulation, leading to mitochondrial impairment, cytoskeletal collapse, and caspase-dependent apoptotic cell death. This study underscores the potential of Paucatalinone A in initiating apoptosis in cancer cells and highlights the therapeutic efficacy of plant-derived agents in treating osteosarcoma, offering a viable approach for managing other intractable cancers.